2013
DOI: 10.1371/journal.pgen.1003755
|View full text |Cite
|
Sign up to set email alerts
|

A Nuclear Calcium-Sensing Pathway Is Critical for Gene Regulation and Salt Stress Tolerance in Arabidopsis

Abstract: Salt stress is an important environmental factor that significantly limits crop productivity worldwide. Studies on responses of plants to salt stress in recent years have identified novel signaling pathways and have been at the forefront of plant stress biology and plant biology in general. Thus far, research on salt stress in plants has been focused on cytoplasmic signaling pathways. In this study, we discovered a nuclear calcium-sensing and signaling pathway that is critical for salt stress tolerance in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 64 publications
(66 reference statements)
0
54
0
Order By: Relevance
“…Interestingly, local adaptation to coastal, potentially saline impacted environments has been shown before, where a sodium transporter allele conferred elevated salinity tolerance (Baxter et al, 2010). Since calcium sensing is a crucial pathway for salt stress tolerance in Arabidopsis (Guan et al, 2013), and has shown to be important for salt and drought stress in rice (Oryza sativa) (Xu et al, 2011), natural allelic variation at the CaS gene locus might be one way in which coastal populations adapt their growth to a saline environment. As such, our findings provide an excellent starting point to study the links between calcium signaling-dependent root growth and adaptation to growth in saline environments.…”
Section: Discussionmentioning
confidence: 85%
“…Interestingly, local adaptation to coastal, potentially saline impacted environments has been shown before, where a sodium transporter allele conferred elevated salinity tolerance (Baxter et al, 2010). Since calcium sensing is a crucial pathway for salt stress tolerance in Arabidopsis (Guan et al, 2013), and has shown to be important for salt and drought stress in rice (Oryza sativa) (Xu et al, 2011), natural allelic variation at the CaS gene locus might be one way in which coastal populations adapt their growth to a saline environment. As such, our findings provide an excellent starting point to study the links between calcium signaling-dependent root growth and adaptation to growth in saline environments.…”
Section: Discussionmentioning
confidence: 85%
“…AtVQ9 protein was exclusively localized in the nucleus, had higher expression at roots and mutation enhanced salt stress tolerance, indicating that AtVQ9 acts antagonistically with AtWRKY8 to mediate salt stress responses (Hu et al 2013). As previously described by Guan et al (2013), AtRSA1 senses salt-induced changes in nuclear free calcium and interacts with a bHLH transcription factor, AtRITF1, which may be phosphorylated by nuclear-localized mitogen-activated protein kinases (MAPKs). The AtRSA1-AtRITF1 complex controls gene expressions which are responsible for Na + homeostasis under salt stress and detoxification of salt-induced reactive oxygen species (Guan et al, 2013).…”
Section: Discussionmentioning
confidence: 87%
“…Previously reported nuclear-localized calcium-binding protein, AtRSA1, was found to regulate the transcription of several genes involved in the detoxification of reactive oxygen species generated by salt stress. It was also found that AtRSA1 (At3g06590) mutant plants were hypersensitive to NaCl but not to LiCl, CsCl, or general osmotic stress (Guan et al, 2013). AtWRKY8 (At5g46350) was mainly responds to high salinity compared to others abiotic stress treatments.…”
Section: Discussionmentioning
confidence: 97%
“…The nuclearlocalized calcium-binding protein, RSA1 (SHORT ROOT IN SALT MEDIUM 1), which is required for salt tolerance, interacts with a bHLH transcription factor-RITF1. This interaction was identifi ed by co-immunoprecipitation, and was further validated by BiFC (Guan et al 2013 ). They have shown that RSA1 and RITF1 regulate the transcription of several genes involved in the detoxifi cation of ROS generated by salt stress and that they also regulate the SOS1 gene that encodes a plasma membrane Na + /H + antiporter essential for salt tolerance.…”
Section: Studying Protein-protein Complexesmentioning
confidence: 82%